Cardiomyopathy in a nutshell: from etiopathogenesis and diagnosis to treatment - Bembey, Raghavi Abhilesh; Babu, Ram (International Journal of Research in Medical Sciences, 2024)
Cardiomyopathy is defined as a heterogeneous group of myocardial disorders wherein the cardiac muscle is functionally and structurally abnormal, without the presence of any congenital heart disease (CHD), coronary artery disease (CAD), valvular disease, and hypertension sufficient enough to lead to abnormality of the myocardium. Based on etiology, cardiomyopathies are classified into primary (acquired, mixed, or genetic) and secondary, which results in different phenotypes like hypertrophic, restrictive, dilated, etc. patterns. Hypertrophic cardiomyopathy is the most common type of primary cardiomyopathy among all cardiomyopathies usually presenting as exertional dyspnea, heart failure, atypical chest pain, syncope, and sudden cardiac death (SCD). Dilated cardiomyopathy is genetic or acquired, causing classic symptoms of heart failure with reduced ejection fraction. Restrictive cardiomyopathy is mostly associated with systemic disease and is rare. Diagnosis of cardiomyopathy includes a detailed evaluation of history, and physical examination followed by a workup including blood test, genetic testing, electrocardiography, and echocardiography testing. Treatment includes initially staging the therapy for heart failure, restriction of physical activity, evaluation of the need for implantable cardioverter-defibrillators, optimization of drugs, and consideration of heart transplantation in refractory cases. Genetic testing of families is now available as an emerging modality for early diagnosis and prevention in relatives of diagnosed cases. This review evaluates the causes, early diagnosis, and early treatment and prevention modalities for cardiomyopathies to reduce morbidity and mortality caused by it.